The moderating effect of environmental regulation and policy on the relationship between continuous process improvement and organizational performance: An empirical analysis - Ghozali Hassan, Mohamad; Diekola Akanmu, Muslim; Yusni Bahaudin, Ahmad (International Journal of Engineering and Technology, 2018)
There have been inconsistencies in the implementation of TQM practices in the Malaysian Food and Beverage Companies and this has led to low sales and less competitive advantage in the industry. This study therefore aimed to investigate the moderating effects of environmental regulation and policy on the relationship between continuous process improvement and organizational performance. A Partial Least Square Structural Equation Modeling (PLS-SEM) was used to estimate the relationship among the above variables in the context of Malaysian Food and Beverage Companies. The results of this study revealed that continuous process improvement has always been a significant predictor of organizational performance by following the regulations and policy related to environment. The results confirmed that environmental regulation and policy moderates the relationship between continuous process improvement and organizational performance. The integration of strategies and practices will help organizations to enhance their performance through implementation of the suggested constructs in this study. The study also supported the premises of the contingency theory and the institutional theory by reaffirming the importance of the supportive environmental regulation and policy for any successful strategic implementationÂ Â